Analisis Persiapan Indonesia dalam Menerapkan Key Audit Matters - Joben Emilio; Melisa Kurniani; Wedi Yanto (Jurnal Mirai Management, 2022)
Abstract This study aims to determine the analysis of Indonesia's preparation in implementing the key audit matters. This research is focused on the enactment of a new accounting standard, namely accounting standard 701 in Indonesia. This research was conducted in analyzing the exposure draft issued by IAPI in 2021 concerning "Communicating Key Audit Matters in The Independent Auditor's Report". The research method use was a qualitative method. The purpose of this study to increase transparency and depth of insight in audits, on the other hand ISA 701 becomes a decision-making framework for deciding which issues will be counted as Key Audit Matters, of course it can help the auditor to limit what matters need attention by considering areas at risk of material misstatements In the financial statements, the auditor must also consider areas in the financial statements that require management's judgment and the impact of the audit on a transaction event in a period. The result of the study was concluded that Indonesia had mature preparations to implement ISA 701. Keywords: Key Audit Matters, Accounting Standards 701, Financial Statements, Audit Opinion